Model Followership pada perusahaan gas LPG Di Bali - Wahyu eko pujianto; Laila ulul ilmi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A number of issues are a challenge for researchers in carrying out qualitative research, one of the techniques that will be used in this qualitative research is interviews, This study aims to model followership several different processes of followers who are willing to follow leaders who will work together to achieve company goals. This research was conducted to determine the followership model in the process at LPG Gas companies in Bali and the relationship between followership and leaders to achieve company goals. Followership is defined as a willingness to work together to achieve the company’s mission, showing good teamwork. Good followership is the foundation of good followership. Very good for achieving effective leadership and achieving company goals. This research was conducted using qualitative methods that apply existing theories on the board follower to dvelop, we need to define the followership contsuct and place it in the context of the followership model theory through interviews with 20 employees who are included in the company's followrship model This research will identify thw followership model theory as research material in the Corporate leadership process.